Stereological study of cerebellar morphology in feline fetuses: Insights from the final gestational stage - de Oliveira, Vinícius Pedro Silva (2025)
This study aimed to conduct a morphoquantitative and stereological evaluation, analyzing the cerebellum of domestic cat fetuses in the latter third of the gestational period. Fetal samples were obtained from a neutering campaign conducted in the municipality of Guarulhos, São Paulo, Brazil. The procedures and protocols used in this work adhere to the guidelines established by the ethics committee of the School of Veterinary Medicine and Animal Science at the University of São Paulo (FMVZ/USP), under the number CEUA 1935251121. The five selected fetuses were fixed in 4 % formaldehyde, and their gestational age was determined by Crown Rump (CR) measurements, followed by an assessment of external characteristics. The cerebella were subjected to the evaluation of morphometric parameters and histological processing using stereology techniques. The obtained means for the cerebellar parameters were as follows: length: 1.0-centimeter, width: 0.54 centimeters, thickness: 0.44 centimeters, and weight: 0.84 g. Using stereology, the following parameters were determined: cerebellar volume, averaging 0.847 cm³; volume density of the cortex: 0.496 or 49 % (molecular layer), 0.0314 or 3.14 % (Purkinje cell layer), 0.232 or 23 % (granular layer), and 0.234 or 23 % (medullary white center). Consequently, the average total volume of the cerebellar cortex is 0.419 cm³ for the molecular layer, 0.026 cm³ for the Purkinje cell layer, 0.196 cm³ for the granular layer, and 0.196 cm³ for the medullary white center. The findings presented here have contributed to an in-depth discussion of the neuro-motor development and cerebellum of domestic cats.